TRANSFORMASI DUSUN SEHAT DAN MANDIRI; INTEGRASI PELAYANAN KESEHATAN HOLISTIK DAN SISTEM INFORMASI DIGITAL UNTUK PENGUATAN EKONOMI LOKAL - Novianty; Muhammad Abadi; Aldalita; Alma Julia; Ilham Ridho Tantowi (DedikasiMU : Journal of Community Service, 2026)
Hamlet 6, Meritai Village, Sungai Pinang District, Banyuasin Regency is a densely populated area far from urban areas. Most of the population earns a living as farmers. Access to health facilities and information system support is also still limited. The purpose of this community service is to create a healthy and independent hamlet through the integration of education, holistic health services, and the use of digital information systems as a basis for strengthening the local economy. The methods used are education, health services, digitalization assistance for MSMEs. The community service was carried out in February 2026 located in Hamlet 06, Sungai Pinang Village, Meritai District, Banyuasin Regency. Participants in this community service were residents in RT 23, RT 24, and RT 25 of Hamlet 6, Sungai Pinang Village, Meritai District, Banyuasin Regency. Educational activities carried out included nutritional information, nursing and midwifery, physiotherapy, waste management. Other activities included health services for blood sugar and HB checks. For MSMEs, digitalization product marketing assistance was provided. These three community service activities are expected to increase community literacy and realize the transformation of healthy and independent villages to improve the local economy.